Protein O-glucosylation: another essential role of glucose in biology - Yu, Hongjun; Takeuchi, Hideyuki (Current opinion in structural biology, 2019)
[Display omitted] •Protein O-glucosylation on EGF repeats is essential for Notch signaling.•POGLUT1 recognizes the properly folded EGF repeats and O-gluco sylates the serine within the consensus sequence C1-X-S-X-(P/A)-C2.•XXYLT1 adds a terminal α3-linked Xyl to Xyl-Glc disaccharides on EGF repeats by an SNi-like retaining mechanism.•O-Fuc and O-Glc glycans stabilize EGF repeats, thereby regulating Notch trafficking. Protein O-glucosylation is an unusual, linear trisaccharide form of O-glycosylation, xyloseα1-3xyloseα1-3glucose1β-O-serine, that is attached to epidermal growth factor-like (EGF) repeats found on numerous proteins including Notch. Genetic and biochemical studies have shown that protein O-glucosylation is essential for full Notch activity in Drosophila and mice. Aberrant protein O-glucosylation has been linked to human diseases. Structural studies of the glycosyltransferases, POGLUT1 and XXYLT1, in complex with substrates revealed the biosynthetic mechanisms of protein O-glucosylation. Very recently, two novel protein O-glucosyltransferases that modify sites distinct from POGLUT1 were identified. Furthermore, protein O-glucosylation turned out to modulate the stability of EGF repeats and thereby regulate Notch trafficking.